Personal and behavioural outcomes of smoking cessation counselling among Malaysian pharmacy students - Saraswathi a/p Simansalam (2015)
The provision of smoking cessation service by Malaysian pharmacists is suboptimal at present despite it being a component of pharmaceutical care. The main aim of this research was to explore the relationship between personal and behavioural factors pertaining to providing smoking cessation counselling among the pharmacy students. There were four related phases in this research; environmental scan, survey of faculty members, pilot and formative studies, and the main study involving Malaysian pharmacy students. From the environmental scan, a gap was identified in the tobacco-related curricula, particularly in smoking cessation counselling skills and behavioural therapy. The survey of faculty members revealed significant differences between the groups of faculty members who had previously received training on providing smoking cessation counselling and those who had not received such training in terms of knowledge, practice, and self efficacy in providing as well as teaching smoking cessation counselling. The pilot and formative studies involved the development and validation of questionnaires used for the main study. The main study involved implementation and evaluation of intervention training for the third- and final-year pharmacy students. Significant improvements, in behavioural performance and personal outcomes including intention, attitude, self efficacy and knowledge for within group (pre-test vs. post-test) and between groups (intervention vs. comparison), were found among the students who participated in this training. It is expected that the intervention would have some influence in terms of smoking cessation counselling practice among these future pharmacists. The findings from this study add to the body of knowledge on tobacco education curricula available in Malaysian pharmacy schools, therefore providing insight for further actions in this area.